Pseudomyxoma peritonei: natural history and treatment. (4th July 2017) - Mittal, Rohin; Chandramohan, Anuradha; Moran, Brendan
Abstract: Pseudomyxoma peritonei (PMP) is an uncommon disease characterised by mucinous ascites, classically originating from a ruptured low grade mucinous neoplasm of the appendix. The natural history of PMP revolves around the "redistribution phenomenon", whereby mucinous tumour cells accumulate at specific sites with relative sparing of the motile small bowel and to a lesser extent other parts of the gastrointestinal tract. Peritoneal tumour accumulates due to gravity and at the sites of peritoneal fluid absorption, namely, the greater and lesser omentum and the under-surface of the diaphragm, particularly on the right. The optimal treatment is complete macroscopic tumour excision termed cytoreductive surgery (CRS) combined with Hyperthermic Intra-Peritoneal Chemotherapy (HIPEC). Total operating time for complete CRS and HIPEC for extensive PMP is around 10 h and generally involves bilateral parietal and diaphragmatic peritonectomies, right hemicolectomy, radical greater omentectomy with splenectomy, cholecystectomy and liver capsulectomy, a pelvic peritonectomy with, or without, rectosigmoid resection and bilateral salpingo-oophorectomy with hysterectomy in females. A unique feature of low grade PMP, which differs from other peritoneal malignancies, includes slow disease progression, which may be asymptomatic until advanced stages. Additionally, very extensive disease with a high "PCI" (Peritoneal Carcinomatosis Index) may still be amenable to complete excision and cure. In cases where complete tumour removal is not feasible, maximum tumour debulking can still result in long-term survival in PMP. PMP is challenging, complex but nevertheless the most rewarding peritoneal malignancy amenable to cure by CRS and HIPEC.